2022
DOI: 10.4314/ejst.v15i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative growth performance and carcass characteristics of guinea fowl (Numida meleagris) and three chicken genotypes

Abstract: A study was conducted to compare the growth performance and carcass characteristics of guinea fowl (GF) with Horro (HR) and Tilili (TL) local chickens, and Potchefstroom Koekoek (PK) exotic chicken. Seventy-five-day-old chicks from each genotype were used in 3 replications in a completely randomized design. Commercial starter and grower feed was fed ad libitum during the 20 weeks of the study. Daily dry matter intake in g/bird was greater for PK (70) than GF (63), HR (59), TL (61). The final body weight (FBW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…Nikolova et al [ 5 ] demonstrated that neither sex nor age affected ( p > 0.05) the pH of breast muscles in guinea fowl, measured 25 min, 4 h and 24 h post mortem. Batkowska et al [ 4 ] and Zelleke et al [ 33 ] found that pH values were higher in leg muscles than in breast muscles, which was also observed in the current study. Previous research conducted by Kiessling [ 47 ] has shown that the lower pH of breast muscles, compared with leg muscles, results from the type and number of muscle fibers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nikolova et al [ 5 ] demonstrated that neither sex nor age affected ( p > 0.05) the pH of breast muscles in guinea fowl, measured 25 min, 4 h and 24 h post mortem. Batkowska et al [ 4 ] and Zelleke et al [ 33 ] found that pH values were higher in leg muscles than in breast muscles, which was also observed in the current study. Previous research conducted by Kiessling [ 47 ] has shown that the lower pH of breast muscles, compared with leg muscles, results from the type and number of muscle fibers.…”
Section: Discussionsupporting
confidence: 90%
“…The weight of giblets in the above study was higher than that noted in this experiment, which could result from differences in slaughter age. Zelleke et al [ 33 ] reported lower gizzard weight (22.4 g) and similar liver weight (17.1 g) and heart weight (6.7 g) in guinea fowl slaughtered at 20 weeks of age, relative to the values determined in the present study. In the work of Bernacki et al [ 32 ], the total weight of giblets in white and pearl gray guinea fowl (45 g and 46 g, respectively) slaughtered at 14 weeks of age was lower than the values noted in this experiment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Musundire et al (2017) reported that Guinea fowls outweighed chickens in terms of having higher body weight, carcass weight, cold dressed weight, and breast weight except for dressing percentage for both species (chickens and helmeted guinea fowls); proportions were comparable. A study by Ahaotu et al (2019) in Nigeria and a survey by Zelleke et al (2022) in Ethiopia reported a higher dressing percentage (75.4 and 73.8 %, respectively) for guinea fowl in comparison with a survey by Musundire et al (2017) in Zimbabwe that found that average was (64.1 %) only. The same trend observed for the breast percentage trait.…”
Section: Carcass Yield and Meat Qualitymentioning
confidence: 69%
“…These include appearance, texture, and flavor. A study by Camas-Robles et al (2020) in Mexico and a survey by Batkowska et al (2021) in Poland reported higher carcass yield percentage (79.30 and 78.77 %, respectively) for guinea fowl in comparison with a study of Zelleke et al (2022) in Ethiopia that found that an average of (73.8 %).…”
Section: Carcass Analysis Techniquesmentioning
confidence: 85%